SERUM LEVELS OF CA 125 IN PATIENTS WITH ORAL SQUAMOUS CELL CARCINOMA (OSCC) AND SUB MUCOSAL FIBROSIS (OSF) AND ITS EXPRESSION IN OSCC TISSUE SAMPLES - Sana Mubarak; Shazia Akbar; Jawad Safdar; Bhunesha Devi; Rubina Gulzar; Syed Faraz (Pakistan Oral & Dental Journal, 2022)
problem is extremely common especially in cosmopolitan cities especially Karachi. The development of premalignant lesion is the first step in initiation of disease process. The proper and early diagnosis of the disease can lead to control and timely treatment of the disease. In the present study CA125 levels in blood were compared in oral squamous cell carcinoma (OSCC) , oral sub mucosal fibrosis (OSF) patients and control (healthy) groups. The expression of CA125 as a marker in OSCC and a premalignant, OSF condition was also analyzed through slides stained with immunohistochemical stain to have an observation of the extent of CA125 expression. Hematological analysis of three groups including two case groups, (OSCC and oral OSF) and one control group was done for CA125 levels. Imunohistochemical staining of slides of different stages of OSCC was performed with the help of specific stain. The hematological analysis of the diseases groups showed difference of values within the threshold level as compare to controls but the ratio of staining was found high in advanced stages of carcinoma as compare to initial stages.The CA125 expression on specimen tissue surface is weak positive. Serum levels of CA125 in participants (cases and controls) of three groups’ i.e. OSCC, OSF and control group were found below threshold levels.